The Effectiveness of Classroom Management Using the Resource Based Learning (RBL) Learning Model on Mathematics Learning Outcomes of Class VIII Students of SMP Negeri 2 Rantau Selatan - Astuti, Kasdianti; Siregar, Sakinah Ubudiyah; Julianti, Eva (Future Science / FSH-PH Publications, 2024)
This research aims to determine the effectiveness of classroom management using the Resource Based Learning (RBL) learning model on student mathematics learning outcomes. This research is Classroom Action research which applies data collection methods through observing learning activities and learning results tests. The research subjects consisted of 36 students in class VIII 4 at SMP Negeri 2 Rantau Selatan for the 2023/2024 academic year. In this research, a significant increase in the effectiveness of classroom management in solving mathematics problems was seen, which was realized through the use of various learning resources such as Student Worksheets (LKPD), mathematics books, internet sources, and teaching aids. This is better than students who receive normal learning. Meanwhile, student learning outcomes were successfully improved by using LKPD using the Resource Based Learning (RBL) learning model. We can see the improvement in students' mathematics learning outcomes from the average score, where there was an increase in cycle I and cycle II. The average score from cycle I was 75.15 and in cycle II was 82.00 with a learning completeness percentage of 66.6%, 93%.